Consumer reactions to high-tech wearable textiles: perceived product importance, consumption benefits and price perceptions - TURHAN, GÜLDEN; Kaplan, Burçin (My University, 2022)
High-tech wearable electronic textiles are emerging technologies that soon seem to become a part of consumers’ lives. In this study, the effects of product type on consumer reactions in accordance with their different consumption benefits such as hedonic, symbolic, and functional were investigated. Price perceptions, consumption benefits in the context of product type, and perceived product importance were expected as determinants of consumer reactions to purchasing high-tech wearable textiles. Data were collected via a structured survey from 327 individuals in Istanbul. The respondents were informed about the product specifications with pictures of Tweet T-shirt, Design Sneakers, and Thermal Cossack. The results, after the factor analysis, ANOVA, correlation tests, and structural equation modeling showed that hedonic, symbolic, and utilitarian benefits affected emotional reaction, but did not affect cognitive reaction and purchasing intention. The hedonic benefit, compared to other benefits, affected emotional reaction more strongly. A significant effect of price awareness was seen on only cognitive reaction. The perceived importance of the product had a strong, positive, and dominant effect on all consumer reactions. With such an effect, it was observed that the possible effects of price and benefit perceptions were eliminated.
Keywords: High-tech wearable textiles; consumption benefits